Transformation in Practice: A Review of Empirical Cases of Transformational Adaptation in Agriculture Under Climate Change - Vermeulen, Sonja J.; Dinesh, Dhanush; Howden, S. Mark; Cramer, Laura K.; Thornton, Philip K. (Frontiers Media, 2018)
Incremental adaptation may be inadequate to deal with rapid shifts and tipping points for food production under climate change. The concepts of transformative and transformational adaptation have emerged in recent years to address the need for major, non-marginal transitions in sectors, such as agriculture in response to climate change. However, there is less empirical evidence of transformation in practice. Here we use a simple semi-quantitative definition to identify recorded cases of transformational adaptation in response to climate change. A structured search of academic literature found 23 empirical case studies that meet our criteria for transformation of agriculture under climate change: a response to climate risks along with a redistribution of at least a third in the primary factors of production (land, labor, capital) or the outputs and outcomes of production over a time period of 25 years or less. The case studies offer experience-based lessons on managing transformative processes in agriculture at all four stages of the adaptation cycle: understanding goals and objectives, developing a vision and pathway, implementing adaptation actions, and monitoring, evaluating and learning. In general, the case-study processes of transformation have diverged from well-managed, inclusive approaches based on foresight and continual learning. Our review provides little early evidence that transformative adaptation processes in response to climate change have generated more resilient agricultural systems or improvements in governance. Governments and development partners could improve the effectiveness of outcomes through providing more comprehensive and long-term approaches to adaptation planning alongside financial and technical assistance, within a framework that rewards farms as multi-functional systems.